Composición florística y estructura horizontal de la vegetación arbórea del arboretum "El Huayo" Loreto-Perú - 2018 - Ruiz Tamani, Willer Eufenio (2019)
In the present work of investigation, the floristic composition and horizontal structure of the arboreal vegetation of the Arboretum "El Huayo" was evaluated whose UTM coordinate of reference is 680659m E and 9576297m N, zone 18S. Datum WGS84, at an approximate altitude of 122 masl. The species-area curve, the Mix intensity, the importance value index of the species and family were determined. To do this, 4 permanent sampling plots of 1.22 ha each were used. In these plots, all individuals with DBH ?5 cm were evaluated, the botanical species, diameter, total height among other dasometric variables were recorded. There were 521 forest species distributed in 183 genera and 53 families. The inflection point of the sample unit according to the area-species curve was not found; the most important species ecologically the Hevea guianensis Aubl; Eschweilera grandiflora (Aubl.) Sandwith; especially the latter, which has the highest IVI value in PPM Nos. 2, 3 and 4. The Lecythidaceae family was the most important in this type of forest; this tells us that it is the best adapted in the heart of the community because it has a higher value of IVI in two of the four evaluated plots.